Poetries - politics : a celebration of language, art, and learning - DeLosSantos, Jenevieve (Rutgers University Press, 2023)
"Poetries - Politics: A Celebration of Language, Art, and Learning celebrates the best of innovative humanities pedagogy and creative graphic design. Designed and implemented during a time of political divisiveness, the Poetries - Politics project created a space of inviting, multilingual walls on the Rutgers campus, celebrating diversity, community, and cross-cultural exchange. This book, like the original project, provides a platform for the incredible generative power of student-led work. Essays feature the perspectives of three students and professors originally involved in the project, reflecting on their learning and exploring the works they selected for the original exhibition. The essays lead to a beautifully illustrated catalogue of the original student designs. Reproduced in full color and with the accompanying poems in both their original language and a translation, this catalogue commemorates the incredible creative spirit of the project and provides a new way of contemplating these great poetic works"-- Provided by publisher.
Keywords: Rutgers University -- Students.; Rutgers University; Posters, American -- New Jersey -- New Brunswick -- Exhibitions.; Social problems -- Posters -- Exhibitions.; Political poetry -- Exhibitions.; Multilingualism -- Study and teaching (Higher) -- New Jersey -- New Brunswick.; Affiches américaines -- New Jersey -- New Brunswick -- Expositions.; Problèmes sociaux -- Affiches -- Expositions.; Poésie politique -- Expositions.; Political poetry; Posters, American; Social problems; Students; New Jersey -- New Brunswick; ART / General.; creative graphic design, graphic design, poetry, Rutgers Mason Gross School of the Arts, graphic design exhibition, Rutgers University, college art, artistic endeavors, celebrating diversity, diversity, pedagogy, language study, humanities pedagogy, poems, college student art, college exhibits, Rutgers admissions, Rutgers alumni, Mason Gross School of the Arts, arts students, Celebration of Language, Language Art and Learning, Arts and Media.; Exhibition catalogs; Electronic books.; exhibition catalogs.; Exhibition catalogs.; Catalogues d'exposition.